FORMULASI SEDIAAN KRIM EKSTRAK ETANOL JAHE MERAH (Zingiber Officinalis var.Rubrum) SEBAGAI ANTIDIABETIC FOOT - faradina, Anniza (Jurnal Penelitian Farmasi Dan Herbal, 2024)
Red ginger is used as a medicinal raw material because it contains 3% oleoresin which has anti-inflammatory, antioxidant, and anti-bleeding properties. In addition, red ginger contains volatile oil (2.58%-2.72%). Red ginger has long been used as medicine to treat a wide range of diseases, including preventing Staphylococcus aureus. Diabetic foot is caused by the pathogenic bacteria Staphylococcus aureus. The purpose of this study was to use experimental research to create a cream formula with ethanol extract of red ginger. Previous research shows that red ginger extract (Zingiber Officinalis Var. Rubrum) has an 80% inhibition zone of 13.11 mm against Staphylococcus aureus bacteria. It can be concluded that Formula 3 (propylene glycol 15%, TEA 3%, oleum rosae drops, cetyl alcohol 3%, and distilled water 50 ml) can be used to make red ginger ethanol extract cream as antidiabetic foot cream.